Application of Radio Frequency Identification for Securing Computer Laboratory Inventory - Prasetyo, Irwan; , Husni Thamrin, S.T, M.T, Ph.D (2014)
These days, there are many identifications using RFID (Radio Frequency Identification) technology. One of the RFID applications is inventory control. It can be used for recording and monitoring the inventory usage activity. Data recording and monitoring of the inventory usage in the laboratory of Faculty of Communication and Informatics still use the conventional system, which is recorded in a file or book manually, unavailability of direct detection when the inventory is taken in and out by the student, and also there is no inventory rental transaction recording. This system provides a solution that solves the problem using RFID technology. The purpose of the research is to improve the effectiveness and efficiency of monitoring and managing the inventory data and recording data of inventory rental transaction. This research uses some methods such as directly interview with laboratory staff, read the literature and get requirement analysis that help researcher to create the inventory management application program. This inventory control uses RFID as an object detector. The object to be identified is laboratory inventory such as a set of computer, access point and router. A tag is embedded inside each item as the identification number of item and it needs to be registered to database. A Subscriber is a student that wants to borrow the laboratory inventory and it must be registered. Rental transaction is an activity in which a subscriber may borrows the inventory that available in the computer laboratory. The results of this research is desktop application that help staff of laboratory to record the data of inventory and students as a subscriber, securing and monitoring the activity of inventory usage and record history of inventory rental transaction, and also provides the accurate data from inventory, subscriber and rental transaction.